History of Hadith Writing, Memorization and Bookkeeping - Ina Alif Hamdalah; Dadang Kahmad (Gunung Djati Conference Series, 2021)
This study aims to discuss the history of writing, memorizing, and recording hadith. This research is a quantitative type using literature study. The results and discussion of this study include writing, memorizing, and recording hadith. This study concludes that the hadith was transferred or spread by word of mouth. The narrators narrated it according to their own memorization and at this time the narrators had not been compelled to record their traditions. The companions in receiving hadith from the Prophet SAW not by writing the hadith in sheets, but holding on to the power of memorization, namely receiving it by rote. Therefore most of the Companions accepted the hadith by listening carefully to what the Prophet said. Then the words and meanings are recorded in their hearts. The person who paid attention to the bookkeeping of the Prophet's hadith was Muhammad bin Muslim bin Ubaidillah bin Shihab az-Zuhri al-Madani Rahimahullah. This research is expected to have benefits as a treasure trove of knowledge for Muslims, and this study recommends that further research be carried out in more depth